Harnessing targeted DNA methylation and demethylation using dCas9. Issue 6 (14th November 2019) - Pflueger, Christian; Swain, Tessa; Lister, Ryan
Abstract: DNA methylation is an essential DNA modification that plays a crucial role in genome regulation during differentiation and development, and is disrupted in a range of disease states. The recent development of CRISPR/catalytically dead CRISPR/Cas9 (dCas9)-based targeted DNA methylation editing tools has enabled new insights into the roles and functional relevance of this modification, including its importance at regulatory regions and the role of aberrant methylation in various diseases. However, while these tools are advancing our ability to understand and manipulate this regulatory layer of the genome, they still possess a variety of limitations in efficacy, implementation, and targeting specificity. Effective targeted DNA methylation editing will continue to advance our fundamental understanding of the role of this modification in different genomic and cellular contexts, and further improvements may enable more accurate disease modeling and possible future treatments. In this review, we discuss strategies, considerations, and future directions for targeted DNA methylation editing.